Research involving Human Subjects - Ethical Perspective - Fakruddin, Md; Mannan, Khanjada Shahnewaj Bin; Chowdhury, Abhijit; Mazumdar, Reaz Mohammed; Hossain, Md Nur; Afroz, Hafsa (Bangladesh Journal of Bioethics, 2013)
Research involving human subjects are important to develop new therapeutics for the betterment of the human race. To take part in such research as volunteers is moral duty of any human. But such experiments should be justifiable and minimal risky for the participants. History of unethical research involving humans led to the development of many guidelines to make such research ethical as well as to gain maximum possible output. Several guidelines have been formulated to ensure research with human participants ethical. All the guidelines emphasize on one thing in particular- informed consent of the human subjects. Other considerations include rational benefit-harm ration, beneficence, justice, adequate research design and approval from proper authorities. All these guidelines aim to prevent any unethical research involving humans against their will. DOI: http://dx.doi.org/10.3329/bioethics.v4i2.16375 Bangladesh Journal of Bioethics 2013; 4(2) 41-48